Subchondroplasty in the Treatment of Bone Marrow Lesions of the Knee: Preliminary Experience on First 15 Patients - Pasqualotto, Stefano; Sgroi, Andrea Vincenzo; Causero, Araldo; Di Benedetto, Paolo; Zorzi, Claudio (Joints, 2019)
Purpose The aim of this prospective study was to assess the effectiveness in terms of pain relief and functional improvement of the Subchondroplasty procedure in the treatment of osteoarthritis-related bone marrow lesions (BMLs) of the knee.Methods The study included first 15 consecutive patients undergone to Subchondroplasty procedure for the treatment of chronic degenerative BMLs in which previous conservative treatment have failed. Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores, Knee Injury and Osteoarthritis Outcome Scores (KOOS), and visual analog scale (VAS) pain scores were obtained preoperatively and at 1, 6, and 12 months of follow-up.Results WOMAC scores significantly improved from 39.7 ± 20.2 before surgery to 26.8 ± 16.1 at the 1-month follow-up (p = 0.045). A further significant improvement to 15.5 ± 12.7 (p = 0.02) and to 8.6 ± 3.1 (p < 0.01) was obtained both at 6-month and at 1-year follow-up. KOOS scores improved significantly from 47.5 ± 16.6 before surgery to 65.4 ± 14.9 at 1 month (p = 0.013) and to 80.4 ± 15.1 at 6-month follow-up (p = 0.01). A further improvement to 85.6 ± 15.1 was recorded 1 year postoperatively, although nonsignificant. VAS score showed a significant improvement from 55.8 ± 20.5 preoperatively to 36.2 ± 16.9 at 1 month (p = 0.008) and to 18.2 ± 17.3 at 6-month follow-up (p = 0.005). This further improved to 12.8 ± 17.9 at 1-year follow-up, although not significantly.Conclusion Subchondroplasty procedure represents a safe and valid surgical option in the treatment of osteoarthritis-related BMLs of the knee, providing an improvement in terms of pain relief and functional recovery. Longer studies are required to evaluate how long these improvements may last.Level of Evidence Therapeutic case-series, Level IV study.
Keywords: bone marrow lesions; subchondroplasty; knee osteoarthritis; calcium phosphate bone substitute